Pathogenesis and intervention strategies for metabolic dysfunction–associated fatty liver disease from the perspective of the gut–microbiota–liver axis - Liao, Jiabao; Zhou, Ze; Lv, You; Zhang, Yiting; Liu, Siyi; Tang, Haixia; Qv, Fei; Wang, Si; Yang, Lianhao; Lu, Yanming; Yang, Zhixia; Xie, Xuehua; et al. (Frontiers in Immunology, 2026)
Trillions of microorganisms in the human gut are important regulators of health, and the gut and liver have a symbiotic relationship with them. The study found that there is bidirectional communication of substances and signals between the gut and liver, and the gut microbiota is an important medium for mediating bidirectional communication in the gut-liver axis. During metabolic dysfunction-associated fatty liver disease (MAFLD) development, the gut microbiota and its metabolites change to different degrees and affect MAFLD pathogenesis through the gut-liver axis. However, the bidirectional communication mechanism between the gut and liver in MAFLD remains unexplored, and further investigation in this domain is warranted. In this review, we summarize the role of the gut-liver axis in the pathogenesis of MAFLD and explore potential therapeutic strategies targeting intestinal microecology (such as probiotic intervention and phage therapy) to provide a theoretical basis for the precise prevention and treatment of MAFLD.